Understanding of penetrating resistance on an inclined plate to cohesive soil using two-dimensional discrete element method - Ge, Jun; Nakashima, Hiroshi; Wang, Xiulun (Frontiers in Built Environment, 2023)
In order to know the effect of varied grousers on the reaction of soil, the reaction of soil by a plate at different angles of inclination using the two-dimensional discrete element method (DEM) has been investigated. The particle-contact model and the calculation algorithm have been calibrated according to the experimental results. Either the simulation or the experiment, a flat iron plate with 5× 77× 100 (mm) was used, and the inclination angle between the plate and the soil surface ranged from 0 to 60 degrees with 15-degree intervals. According to the result, the values of the root mean square error between the simulation and the experiment were found as 6.62, 36.60, 58.63, 60.84, and 66.25 N for inclination angles from 0 to 60 degrees in the horizontal direction. Moreover, the RMSE values of 127.91, 216.06, 75.88, 110.40, and 25.49 N were obtained for the vertical direction. Overall, a minimal discrepancy was observed between the results of DEM simulation and those of experiments in the vertical component of reaction force when the inclination angle of the plate was increased. Meanwhile, the result in the horizontal component did not agree with that of the experiment according to the varied inclination angles.